Buletin Peternakan : PROTEKSI MINYAK IKAN LEMURU, MINYAK KELAPA SAWIT, DAN BUNGKIL SAWIT TERHADAP pH DAN NH3 DALAM RUMEN SAPI PERANAKAN ONGOLE - Catur Suci Purwati (Peternakan UGM, 2016)
The aimed of this research is to know the influence of protection lemuru oil, palm oil, and palm oil cake to pH and NH3in the rumen of the Ongole